Oxidation of Iodine to Dihaloiodate(I) Salts of Amines With Hydrogen Peroxides and Their Crystal Structures - Prinčič, Griša Grigorij; Maselj, Nik; Goreshnik, Evgeny; Iskra, Jernej (Frontiers in Chemistry, 2022)
Herein we report a general preparation of dihaloiodate salts of heterocyclic amines (tertiary and quaternary) with sterically accessible and hindered nitrogen atom. A number of such compounds were prepared from preformed HICl2 or HIBr2 formed in situ by the reaction of corresponding hydrogen halide, iodine and H2O2. The salts of DABCO and its methylated derivatives, HMTA, DBU and 2,4,6-tri-tert-butylpyridine were obtained in excellent yields and their structure determined by NMR and Raman spectroscopy and single crystal X-ray diffraction. Non-hindered bases like DABCO, HMTA and DBU formed IX2− salts that decomposed further to complexes with interhalogen compounds due to formation of N…X halogen bonds. The dihaloiodiate(I) salts of sterically hindred 2,4,6-tri-tert-butylpyridine were stable. Its dibromochlorate(I) salt was also prepared via a different synthetic method with N-chlorosuccinimide as an oxidant.